Studies on Ottoman social and political history : selected articles and essays - Karpat, Kemal H. (Social, economic, and political studies of the Middle East and Asia, 2002)
This work comprises a collection of articles and essays published in a variety of journals, which seek to identify and analyze the internal forces which transformed the Ottoman State into a variety of national states in the Balkans and the Middle East.